The Human Concept in Transpersonal Psychology - Aziz, Al Fira Elisa (Maliki Interdisciplinary Journal, 2025)
Transpersonal psychology is a brach of psychology that integrates psychological espects with spirituality. The main concept is the existence of a self-identity that transcends physical boundaries and is closely connected to the spiritual realm, where the highest human potential is believed to be rooted. This field emphasizes consciousness and spiritual experiences, including transcendence, and understands humans not only as physical entities but also as spiritual beings. Transpersonal psychology was developed from the humanistics theory and explores aspects such as mystical experiences, meditation, and parapsychological phenomena like extrasensory perception. Key figures in transpersonal psychology include Abaram Maslow, William James, and Ken Wilber. These figures developed methods that focus on uncavering human potential and higher consciousness. This field covers various scopes, including consciousness, spiritual potential, and ego transcendence. Thus, transpersonal psychology aims to explore deeper dimensions of humans consciousness, integrating physical, emotional, intellectual, and spiritual aspects to enhance self-development and interpersonal relationships.